2022
DOI: 10.1201/9781003218654
|View full text |Cite
|
Sign up to set email alerts
|

Remanufacturing and Advanced Machining Processes for New Materials and Components

Abstract: Reasonable efforts have been made to publish reliable data and information, but the author and publisher cannot assume responsibility for the validity of all materials or the consequences of their use. The authors and publishers have attempted to trace the copyright holders of all material reproduced in this publication and apologize to copyright holders if permission to publish in this form has not been obtained. If any copyright material has not been acknowledged please write and let us know so we may rectif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 340 publications
(538 reference statements)
0
3
0
Order By: Relevance
“…In the present study, the initial powder materials were portioned in a way that provides the final phase composition with proportions 60 wt.% of Al 2 O 3 , 25 wt.% of mullite, and 15 wt.% of ZrO 2 . Moreover, previous studies on alumina–zirconia–mullite composites, as well as research on sintering of alumina and zirconia, reported better sintering ability and enhanced properties of this composite in the abovementioned proportion [ 33 , 34 , 35 ].…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…In the present study, the initial powder materials were portioned in a way that provides the final phase composition with proportions 60 wt.% of Al 2 O 3 , 25 wt.% of mullite, and 15 wt.% of ZrO 2 . Moreover, previous studies on alumina–zirconia–mullite composites, as well as research on sintering of alumina and zirconia, reported better sintering ability and enhanced properties of this composite in the abovementioned proportion [ 33 , 34 , 35 ].…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…Prosedur pembuatan terlibat langsung dengan modifikasi bentuk, dimensi, dan kualitas tertentu suatu bagian. Pemotongan, penggilingan, pembengkokan, penempaan, perlakuan panas, pengeleman, mematri, pengelasan, kebiruan, pengelasan difusi, etsa industri, elektrolisis, pengerasan dalam dan permukaan, pengelasan eksplosif, pemotongan jet air, peledakan pasir, dan pengolahan arus frekuensi tinggi, semuanya dapat digunakan untuk mencapai tujuan [3].…”
Section: Pendahuluanunclassified
“…This human interaction in analyzing and interpreting such reports can cause unpredictability in the manufacturing process. Besides that, the ability to control all the machining process variables has surpassed human limits, delegating to machines and intelligent systems a good part of the tasks that ensure precise manufacturing [5].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complex interrelationships between various factors that compose the journal-bearing housing manufacturing process, techniques based on machine learning have become essential tools due to their speed, robustness, and non-linear characteristics when working with data. These techniques sustain the intelligent utilization of manufacturing resources and the adaptive adjustment of manufacturing processes that support an organization called smart factories [5].…”
Section: Introductionmentioning
confidence: 99%